USE OF GENETIC ALGORITHMS IN CREATING OIL BLENDS REQUIRED FOR REFINERY DISTILLATION PLAN - Reem Sabah Mohammed; Marius Banica; Renata Rădulescu; Timur Chis (Romanian Journal of Petroleum & Gas Technology, 2022)
In Romania, the oil refineries were designed to process the crude oil extracted from the deposits located in their immediate vicinity (Suplacu de Barcău Refinery, 1 Mai Refinery, Câmpina Refinery, Vega Refinery and Dărmănești Refinery), to process crude oil imported from external oil basins (Onești Refinery, Brazi Refinery, Teleajen Refinery, Midia Refinery and Pitești Refinery) and to process crude oil from the Muntenia and Oltenia oil basins (Brazi Refinery and Pitești refinery). The closing of some refineries after 1990, the reduction of crude oil imports and especially the tightening of the quality conditions of the delivered petroleum products (the need to reduce the sulphur content of petroleum products, the use of bio-fuels) led to the reconsideration of deliveries to the refineries that remained in operation, through the creation of mixtures of crude oils extracted from Romania (for the Brazi Refinery) and the import of crude oil mixtures for the Teleajen and Midia Refineries, which would ensure the new quality conditions of finished petroleum products. The article describe how to create crude oil blends according to refinery requirements, using both classical estimation methods and genetic algorithms to determine the variation in the properties of these blends.